Base isolation for near fault motions. - Jangid, R.S.
Three analytical studies of base isolated structures are carried out. First, six pairs of near fault motions oriented in directions parallel and normal to the fault were considered, and the average of the response spectra of these earthquake records was obtained. This study shows that in addition to pulse type displacements, these motions contain significant enegy at high frequencies and that the real and pseudo velocity spectra are quite different. The second analysis modelled the response of a model of an isolated structure with a flexible super structure to study the effect of isolation damping on the performance of different isolation systems under near fault motion. The results show that there exists a value of isolation system damping for which the superstructure acceleration for a given structural system attains a minimum value under near fault motion. Therefore, although increasing the bearing damping beyond a certain value may decrease the bearing displacement, it may transmit higher accelerations into the superstructure. Finally, the behaviour of four isolation systems subjected to the normal component of each of the near fault motions were studied, showing that EDF type isolation systems may be the optimum choice for the design of isolated structures in near fault locations.
Keywords: Base isolation; Base displacement; Comparative performance; Earthquake; Near fault; Optimum damping; Superstructure acceleration